Intergenerational Solidarity and Satisfaction With Life: Mediation Effects With Emerging Adults - Coimbra, Susana; Mendonca, Marina Goulart (Paidéia (Ribeirão Preto), 2013)
The increasing dependency of emerging adults (EA) on their family of origin and their lower future expectations challenge intergenerational family support exchanges and may affect their impact on satisfaction with life. This study aims to examine the mediation effect of familism, filial maturity, and relationship satisfaction between different directions of support (received, given and anticipated between both) and satisfaction with life. Data was collected through the administration of self-report questionnaires to a convenience sample of 243 EA (18-30 years old) of both genders, students and workers, of different socioeconomic statuses. Results corroborate the mediation effect of the study variables and suggest that the magnitude of this impact depends on the direction of the support: partial mediations are observed for the received support, whereas total mediations are observed for the given support.